The Contribution of Outdoor Education Activities to Enhance Indonesian Bullying Victims’ Resilience - Vicki Ahmad Karisman; Moch. Asmawi; Samsudin (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
This study is objectively intended to recognize the contribution of outdoor education activities on the students’ resilience. Appropriate interventions are needed to enhance the resilience of elementary school students in the effort to overcome bullying. This study employed an experimental method with a one-group pretest-posttest design. The study’s participants consisted of 278 students (187 males of an average age of ±11.4 years, 91 females of an average age of ±11.6 years) from four schools at Cimahi. This study is an experimental research with one-group pretest-posttest design. Interventions were administered in 2-hour meetings over a 14-week period. The outdoor education activities implemented as interventions included hiking, climbing, orienteering, outdoor game, and camping. The research instrument employed was the Resilience Scale. The Paired Sample Test showed the significance level 0,000 < 0,05, it means that there was a significant improvement in the elementary school students’ resilience gained through the outdoor education activities. By this improvement, it is expected that outdoor education activities can equip the students psychologically to overcome any kind of bullying demeanor. In conclusion, the outdoor education activities could enhance the bullying victims’ resilience as the result showed that the implementation of outdoor education activities significantly effects on the students’ resilience.